Surfactant protein–d amino acid variants and their associations with metabolic, oxidative stress, infection and quality of life parameters in patients with type 2 diabetes mellitus in Pakistan - Javed, Shireen (2025)
Type 2 diabetes mellitus (T2DM) is prevalent in Pakistan, and often linked to recurrent infections and poor quality of life. Oxidative stress, surfactant protein-D (SP-D), and its rs721917 SNP may contribute to this risk, but no studies have investigated this association in Pakistan. Hence, this study investigated rs721917 SNP variants and their links with metabolic, oxidative stress, infection, and quality of life parameters in T2DM patients. A case-control study was conducted at Aziz Fatimah Hospital, Faisalabad, Pakistan. Using non-probability purposive sampling technique, 170 participants (86 T2DM, 84 Controls; aged 30–65 years) were recruited. Blood samples were tested for SP-D-, Fasting Blood Sugar (FBS), glycated haemoglobin (HbA1c), malondialdehyde (MDA), and superoxide dismutase (SOD) activity. DNA was extracted and amplified by polymerase chain reaction. Sanger sequencing was done to identify the rs721917SNP genotypes. The TC genotype was significantly more prevalent in T2DM patients (p<0.001). SP-D levels were lower in T2DM patients (p=0.014), with higher FBS, HbA1c (both p<0.001), and MDA levels (p=0.012), and reduced SOD activity (p=0.022) compared to controls. SP-D showed significant negative associations with FBS (p=0.001), HbA1c (p=0.032), and MDA (p=0.014). The TC genotype had significantly lower SP-D levels (p=0.040) and SOD activity (p=0.044) compared to TT and CC genotypes. FBS, HbA1c, and MDA levels were higher in TC, followed by CC, versus TT (p=0.006, 0.001, 0.037 respectively). Both TC and CC genotypes showed a three-fold higher oxidative stress risk than TT wild type (p=0.044, 0.041 respectively). Infection rates were higher in T2DM patients (p<0.001), particularly among TC carriers, who had a four-fold higher infection risk (p=0.013). T2DM patients, especially females, showed poor quality of life with Physical Component Summary and Mental Component Summary < 50. No significant impact of SP-D levels and rs721917 was found on quality of life. In conclusion, TC genotype of rs721917 of SP-D was the most common genotype and an independent predictor of oxidative stress and infections in T2DM patients in Pakistani population which were linked with low SP-D levels and SOD activity as well as with high FBS, HbA1c and MDA levels. In addition, T2DM patients also exhibited poor quality of life which was not associated with SP-D levels and rs721917 SNP. Hence, it is plausible to suggest that doing SP-D gene analysis can provide early management and protection against infections in T2DM and further studies are needed to assess the potential use of SP-D as a useful therapy for prevention or treatment of infections in T2DM